Evaluation of organizational culture in enterprises in the Czech Republic using OCAI - Balková, Miluše; Jambal, Tsolmon (Frontiers in Psychology, 2023)
The goal of this work was to use the OCAI diagnostic method to find out the existing and preferred organizational culture in companies in the Czech Republic and then to evaluate their dependence on the size of the organizations. Data were collected in 2019-2021 and evaluated using Microsoft Excel and IBM SPSS 24 statistical program, e.g. descriptive statistics tools, one-sample z-test, analysis of variance and post hoc test (Tukey's honest significant difference - HSD). The research was conducted on a sample of 962 companies across the entire republic and fields. The results of the study show that clan culture prevails in the Czech Republic, which was dominant in all six dimensions. Enterprises in the Czech Republic have a mix of organizational cultures in the following order: 1. clan culture (31.72%) 2. hierarchical culture (25.46%) 3. market culture (21.5%) and 4. adhocratic culture (21.28 %). However, with regard to the desired cultural mix, this order changes as follows: 1. clan (35.3%) 2. hierarchical (22.91%) 3. adhocratic (22.63%), and 4. market culture (19.17%) ). Furthermore, it was found that a statistically significant difference was observed in the assessment of organizational culture depending on the size of the organization in the Czech Republic. A limitation of the research could be the unequal number of respondents in 2020 and 2021, which does not allow comparing differences in the time period. This work can serve as a comparative basis of organizational culture with another national culture.